Security Reform of France African Policy Cooperation: Incremental process - (:unkn) unknown (My University, 2019)
The first generation of cooperation agreements and their security clauses in Francophone Africa was bilateral. The specific characteristic of such clauses was the secret component of part of the defense and security agreements, often applied according to the "away from the public eye" principle. The concept of bilateral cooperation translated into ensuring the security of the African countries, the regimes in place and the French interests in the face of external and internal threats. It was a matter of ensuring Francophone Africa's political stability, homogeneity and coherence, which would be favourable to French and African partners transactions. This kind of bilateral agreement was much criticized and contested. On the one hand, it was considered as being allegedly a "reproduction of colonial relations" favourable to "Françafrique" network. On the other hand, it met with increasing competition from the great powers as well as from emerging powers. Its decline was also due to multiple levels and stakeholders of international relations and global democratisation. Interdependencies are being intensified, setting off "reverse" flows of influence from African players to French African policy. The context of this evolved contestation and new geopolitics is mainly increasing multilateralism; emergence of regionalism; development of European defense and diplomacy; fight against terrorism and burden sharing reorganization. The aim of this article is to clarify how the second generation of cooperation agreements and their security clauses reforms is a part of an incremental reform process. Financial and economic crisis are tightening French cooperation and defense budgets. "Behind the economic crisis, the political crisis" is appearing in Africa just as it is within its partners. Diplomatic, budgetary and security dynamics are thus forcing France, on the one hand to explore substitution strategies, including coalition and on the other, to prioritise its all
Keywords: African Research